Implementation of smart devices in health crisis scenarios: risks and opportunities - Roberto Losada Maestre; Rubén Sánchez Medero (Frontiers in Political Science)
The scarcity of healthcare resources, particularly during crises, is a reality. AI can help alleviate this deficiency. Tasks such as triage, diagnosis, or determining a patient’s life-threatening risk are some of the applications we can delegate to algorithms. However, the limited number of real clinical experiences and the lack of research on its implementation mean that we only partially understand the risks involved in its development. To contribute to the knowledge of both the opportunities and risks that a management solution like AI presents, we analyze the case of autonomous emergency vehicles. After conducting a detailed literature review, we adopt an innovative perspective: that of the patient. We believe that the relationship established between the patient and this technology, particularly the emotional connection, can determine the success of implementing such autonomous driving devices. Therefore, we also propose a simple solution: endowing this technology with anthropomorphic features.